Toward a Globally Harmonized System: Negotiating to Promote Public Health, Environmental Protection, and International Trade - Lowe, Mary Frances (Tufts Archival Research Center, 2005)
Volume 27, Issue 1. Winter/Spring An EPA official discusses the lessons of a complex, ambitious, and technical negotiation process that led to international voluntary agreements on a Globally Harmonized System for Classification and Labeling of Chemicals.